Tożsamość społeczna a dobrostan psychiczny ludzi młodych w czasie pandemii COVID-19 - Maciąg, Rafał (Kultura-Społeczeństwo-Edukacja, 2024)
The concept of identity refers to the relatively permanent identification of an individual, and in the context of mental well-being, this self-definition may undergo significant changes. During the COVID-19 pandemic, remote learning was ordered and social contacts were limited, which caused emotional distress, symptoms of anxiety and depression, and a sense of loneliness and depression among young people. These phenomena have been reported independently in different parts of the world, although the research conducted during the COVID-19 pandemic differs in its assumptions and methodology. The aim of the paper is a comparative analysis of selected research on the mental health of young people during the pandemic. The assumption of this analysis is that young people experienced a breakdown in their mental well-being during an important period of building their identity. Membership in peer groups is most fully manifested in participation in real events, and during the pandemic, managed isolation was a threat to the construction of individual and social identity. The study proves that during the period that the rates of depression increased among teenagers, especially among young women. This corresponds to higher use of social media than ever before.